Inkonstitusionalitas Pasal 19 Perma Nomor 2 Tahun 2016 dan Implikasinya terhadap Akses Keadilan Warga Negara - Yogi Zul Fadhli (Jurnal Konstitusi, 2016)
Judicial review as an extraordinary legal effort has constitutionally regulated by Indonesian law. However, in the administrative court, related with the dispute of location determination for the public interest, judicial review is dispensed by the Article 19 of Supreme Court Regulation No. 2 of 2016. Those article is unconstitutional because theoretically contrary with the Constitution of Indonesia and disharmonious in the types, hierarchy and substantive of the proportionality principle. Thus, human rights violation is rising especially for the people that being victims of land grabbing of development project for the public interest and disorganize of the system procedures in administrative court.